2009
DOI: 10.1108/02686900910948170
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, firm characteristics and risk management committee formation in Australian companies

Abstract: Purpose -The purpose of this paper is to examine how a risk management committee (RMC), as a newly evolving sub-committee of the board of directors, functions as a key governance support mechanism in the oversight an organisation's risk management strategies, policies and processes. However, empirical evidence on the factors associated with the existence and the type of RMCs remains scant. Design/methodology/approach -Using an agency theory perspective, this study investigates the association between board fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
2
41

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(222 citation statements)
references
References 40 publications
5
151
2
41
Order By: Relevance
“…In addition, risk committees could be expected to be even more important for firms in such industries that involve higher levels of uncertainty, or in other words, risk (Tao & Hutchinson, 2013). Similarly, Subramaniam et al (2009) show that the need for risk management committees varies with board size. Nkoko and Tesfaye (2014) www.ccsenet.org/ijef…”
Section: Early Determination Of Risk Committeesmentioning
confidence: 99%
“…In addition, risk committees could be expected to be even more important for firms in such industries that involve higher levels of uncertainty, or in other words, risk (Tao & Hutchinson, 2013). Similarly, Subramaniam et al (2009) show that the need for risk management committees varies with board size. Nkoko and Tesfaye (2014) www.ccsenet.org/ijef…”
Section: Early Determination Of Risk Committeesmentioning
confidence: 99%
“…Specifically, establishing corporate governance practices may flag the firms' commitment to better governance. As a result, it is expected to minimise any potential risk of investors' devaluation of the firm (Subramaniam, McManus and Zhang, 2009). There is no current mandatory regulatory requirement for establishing a RMC in Australia.…”
Section: Signalling Theorymentioning
confidence: 99%
“…In the first stage, a probit regression was conducted. The dependent variable was a RMC, and similar to previous research, the test included board size, CEO duality, and board independence, as the previous studies have indicated that these three variables influence firms' establishment of a RMC and separate RMC (Hines and Peters, 2015;Ling, Zain and Jaffar, 2014;Subramaniam, McManus and Zhang, 2009). Using the parameters from this model, the inverse Mills ratio was computed for all sample firms (Heckman, 1978;Johnston and DiNardo 1997).…”
Section: Heckman (1978) Test -Self-selection Bias (Endogenous Issues)mentioning
confidence: 99%
See 2 more Smart Citations